ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI MEDIASI ( STUDY DI WILAYAH KEC.PURWOREJO KOTA PASURUAN ) - Sumarno Sumarno; Muryati Muryati; Kuncoro Kuncoro (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to obtain empirical evidence of the ability of transformational leadership styles and motivational abilities in improving employee performance, either directly or through job satisfaction mediation.This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 78 subdistrict employees (seven subdistrict) in the Purworejo District, Pasuruan City.Empirical evidence shows that both transformational leadership style as well as motivational styles are able to increase employee performance, either directly or through job satisfaction mediation. This finding is supported by the descriptions of the four variables, all of which were obtained from high responses, including showing self-confidence, salary sufficient for living necessities, job satisfaction in this agency, and trying to achieve work targets.This research has made various efforts to reduce or eliminate the occurrence of "plagiarism", both data and others.